A formação e a permanência de professores mestres e doutores nas escolas públicas estaduais de São Paulo: o programa Bolsa Mestrado/Doutorado - Rocha, Francisco Antônio Moreira (2012)
The purpose of this research has as objective to analyze the contributions and impacts of Masters / PhD Scholarship, from the initial question What is the contribution of the PBM / D and its impact on personal development, professional teachers and professional recovery of basic education by SEE-SP, after completion of graduate studies. We assume the configuration of this research from the documentary analysis and semi-structured qualitative character, the concern is with the quality in the interviewees' statements, as well as documentation. The search for answers to some personal questions in order to explain a professional education with academic education, in addition to that required for a position as teacher of Basic Education II, SEE-SP and that went through one of the types of continuing education through PBM / D, teacher Master or PhD in public schools, found the Internet, the sites of SEE-SP, APEOESP lattes and curricula of Fellows and Board of Education 1 North, documents the laws of the past three decades, records registration form sheets and monthly reports submitted for analysis of the regional commission. As conclusion, we present what we consider relevant in an enterprise investigative searching for answers to the survey answers and points, a potential of PBM / D for personal and professional training, as well as for its recovery as a teacher at the school, with its students, but adds the lack of public policies to enhance the professional teacher and researcher